Asthma With Bronchial Hypersecretion: Expression of Mucins and Toll-Like Receptors in Sputum and Blood [Corrigendum] - Crespo-Lessmann A; Mateus E; Torrejón M; Belda A; Giner J; Vidal S; Sibila O; Plaza V (Journal of Asthma and Allergy, 2025)
Crespo-Lessmann A, Mateus E, Torrejón M, et al. J Asthma Allergy. 2017;10:269–276. Page 269, Abstract, Materials and methods section, line two, the text “19 with bronchiectasis” should read “19 with bronchial hypersecretion”. The authors apologize for this error.